Penerapan Taguchi Parameter Design dalam Penentuan Level Faktor Produksi Batako untuk Memaksimumkan Kekuatan Tekan (Studi Kasus di Balai Besar Keramik) - Wawolumaja, Rudy; Faurika, Ridani (Zenit, 2012)
According to preliminary research conducted at Balai Besar Keramik, it is found out that “Batako Padalarang” products  available in the market are still below the Indonesian National Standard requirement (SNI 03.2113.91). This research  is conducted to obtain optimum process parameters to meet  the  requirements of Indonesian National Standard. The method  used is Taguchi Parameter Design to fulfill the criteria for compression strength of Indonesian National Standard. From the analysis of Taguchi method, we get to know that the factors and level that affect the batako’s strength of compressive significantly are factor A (forming pressure) with level 2 (4  ton),  factor B (material composition) with level 1 (1 : 3), factor C (texture of tras) with level 1 (0,3 mm), factor D (mixing time) with level 2 (10 minutes), factor E (water percentage) with level 2 (15%), and factor F (curing time)  with level 3 (28 days). And from the confirmation experiment we get percentage of increase after using Taguchi method amounting to 72.75% and the decrease of loss 92.82%. Keywords : Taguchi, batako, loss fuction